2013
DOI: 10.1152/jn.00774.2012
|View full text |Cite
|
Sign up to set email alerts
|

Pinprick-evoked brain potentials: a novel tool to assess central sensitization of nociceptive pathways in humans

Abstract: Although hyperalgesia to mechanical stimuli is a frequent sign in patients with inflammation or neuropathic pain, there is to date no objective electrophysiological measure for its evaluation in the clinical routine. Here we describe a technique for recording the electroencephalographic (EEG) responses elicited by mechanical stimulation with a flat-tip probe (diameter 0.25 mm, force 128 mN). Such probes activate Aδ nociceptors and are widely used to assess the presence of secondary hyperalgesia, a psychophysic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 53 publications
5
67
1
3
Order By: Relevance
“…Electroencephalography, in contrast, is a non-invasive neurophysiological method that records the electrical activity of the brain at the scalp, largely from superficial regions, such as the somatosensory cortex, because voltage changes dissipate from deeper subcortical structures over a certain distance. It is possible to observe event-related changes in the EEG traces following certain stimuli, including noxious laser, pinprick and heel lance (Zhang et al 2012;Fabrizi et al 2013;Iannetti et al 2013). Recently, studies have identified an event-related potential in newborn infants and infants up to 1 year old, which is specific to noxious stimulation (Slater et al 2010b,c;Fabrizi et al 2011;Verriotis et al 2015).…”
Section: Infant Pain and The Cerebral Cortexmentioning
confidence: 99%
“…Electroencephalography, in contrast, is a non-invasive neurophysiological method that records the electrical activity of the brain at the scalp, largely from superficial regions, such as the somatosensory cortex, because voltage changes dissipate from deeper subcortical structures over a certain distance. It is possible to observe event-related changes in the EEG traces following certain stimuli, including noxious laser, pinprick and heel lance (Zhang et al 2012;Fabrizi et al 2013;Iannetti et al 2013). Recently, studies have identified an event-related potential in newborn infants and infants up to 1 year old, which is specific to noxious stimulation (Slater et al 2010b,c;Fabrizi et al 2011;Verriotis et al 2015).…”
Section: Infant Pain and The Cerebral Cortexmentioning
confidence: 99%
“…Instead of applying the pinprick stimulus as fast as possible as in the study of Iannetti et al (2013), the pinprick stimulus was applied and removed slowly and maintained against the skin for at least 1 s. The reason for doing this is that the actual force that is applied onto the skin is dependent on the velocity at which the stimulus is delivered. To be sure that the actual delivered force is the same as the planned force, the pinprick stimulus should be applied onto the skin in a slow fashion (www.mrc-systems.de/ englisch/products/pinprick.html).…”
Section: Pinprick Stimulationmentioning
confidence: 99%
“…It would thus be of great value to have a noninvasive clinical and research laboratory tool that is able to reliably assess sensitization of mechanical nociceptive pathways. One of these tools could be the recording of pinprick event-related brain potentials (ERPs).IRecently, Iannetti et al (2013) recorded for the first time ERPs elicited by mechanical pinprick stimulation before and after intradermal injection of capsaicin in the area of secondary hyperalgesia in healthy volunteers. The mechanical pinprick stimulation was performed by quickly applying and removing a sharp-tipped probe (0.25-mm diameter).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Iannetti et al (2013) recorded ERPs in response to pinprick stimulation before and after intradermal injection of capsaicin in the adjacent skin. The pinprick stimulation elicited a typical biphasic ERP waveform (N1 and P2 waves) with latencies compatible with the conduction of myelinated A␤-or A␦-fiber afferents.…”
Section: Effect Of Hfs On the Responses To Mechanical Stimulimentioning
confidence: 99%